EVALUATION OF BASIC FINANCIAL STATEMENTS UNDER TAS-27 AND IAS-27 - Erkan, Gulgun (European Scientific Journal, ESJ, 2012)
As of 01/01/2005, all companies which are operating in member states of the European Union and whose securities are publicly traded are required to prepare their consolidated balance sheets, which is one of the financial statements, according to the provision set by the international accounting standards. Since Turkey is in the process of accession to the European Union, all companies listed on the stock exchange should use a common international accounting language in their financial reports. This situation requires compliance with international standardization in the field of accounting. In this study, TAS/IAS-27 "Consolidated and Separate Financial Statements Standard" was examined and consolidation operations necessary for preparation of consolidated balance sheets and consolidated income statements are explained.